(untitled) (Perner’s Contacts, 2010)
This article aims to familiarize with the procedure of measurement of passenger satisfaction and quality evaluation of public transport. The described method is intended to universities and research organizations for their scientific work they need current data on passengers and repositioning relations in public transport. It is also intended to be used by public transport providers to measure passenger satisfaction and assess the quality of their services.